The use of video-based interventions to teach activity of daily living to children with autism spectrum disorder–scoping review - Ismail, Nurul Khairani; Hosshan, Hasrul; Abd Aziz, Nurbieta; Masnan, Abdul Halim; Che Rozubi, Norsayyidatina; Md Zalli, Mohd Muslim; Arifin, Siti Roshaidai Mohd (Intelektual Pustaka Media Utama, 2024)
The study aimed to delve into the successful implementation of Video-Based Intervention (VBI) in improving activity of daily living skills (ADL) among children with autism spectrum disorder (ASD). Three primary electronic databases were utilised to perform this review: WOS, Scopus and Google Scholar. The process primarily used the research methodologies by Arksey and O'Malley as a framework. In the course of performing the scoping review, three themes emerged: firstly, a wide range of VBI techniques can be employed to enhance the skills of children with ASD; secondly, when VBI is coupled with adequate implementation support specifically tailored for children with ASD, it can effectively improve their daily living abilities. Essentially, the findings of this study support that VBI implementations can promote desired skills in ADL among children with ASD. Furthermore, additional implementation support complements video modeling, improving skill acquisition in ASD. This research enhances the existing knowledge base dedicated to enhancing the quality of life for children with ASD, providing valuable insights for educators, clinicians, and families involved in their care.